Quantum Groups in Nuclear Spectra and in Metal Clusters - Bonatsos, Dennis; Kotsos, B. A.; Raychev, P. P.; Terziev, P. A. (HNPS Advances in Nuclear Physics, 2019)
Quantum algebras (quantum groups), which are nonlinear generalizations of the usual Lie algebras, provide a rich variety of symmetries finding applications in the description of several physical systems [1]. Using irreducible tensor operators under sug(2) a rotationally invariant Hamiltonian which provides a good description of nuclear rotational spectra is constructed and its relation to existing nuclear models is considered. Using the same techniques a 3-dimensional ç-deformed harmonic oscillator with ug(3)Dsoq(3) symmetry is constructed, compared to the modified oscillator of Nilsson, and used for the successful description of magic numbers [2] and supershells [3] in metal clusters.